BEIJING DECLARATION AND WOMEN’S PROPERTY RIGHTS IN NIGERIA - Folarin, Sheriff F.; Udoh, Oluwakemi D. (European Scientific Journal, ESJ, 2014)
In Nigeria, women have suffered various forms of discrimination and oppression during property sharing, especially in terms of land for economic purposes and other physical assets. The challenge has been that, in patriarchal societies, like Nigeria, women are regarded as subservient to men and are never considered in property sharing. Rather, the woman is often regarded as part of the property to be shared especially during the loss of her spouse. Most disturbing is that, though statutory law and international laws have affirmed women’s rights to land and other property, women are often denied access and ownership to property due to unfavorable customary practices. This paper examines women’s property rights in Nigeria. In doing so, it looks critically into Nigeria’s compliance with the 1995 Beijing Platform of Action. It also identifies some factors such as customary and statutory laws as responsible for the discrimination of women vis-à-vis their rights to property and inheritance. In addition to these, it concludes that, the 1995 Beijing Declaration is yet to be fully integrated and domesticated in the national legislations that protect women and their rights to property. In carrying out this research, secondary sources were consulted. Recommendations were made bordering on equality between men and women and gender-sensitivity in legal institutions.